Hyperbolically embedded subgroups and quasi-isometries of pairs - Hughes, S; Martínez-Pedroza, E (Cambridge University Press, 2023)
We give technical conditions for a quasi-isometry of pairs to preserve a subgroup being hyperbolically embedded. We consider applications to the quasi-isometry and commensurability invariance of acylindrical hyperbolicity of finitely generated groups.